Performance of the far infrared and conventional oven drying methods in extraction of acetaminophen from Aquilaria spp dried leaves / Habsah Alwi - Alwi, Habsah (2023)
The growing of Aquilaria plantation in Malaysia has become an interest among researchers to explore additional benefits while waiting for the tree to produce a good quality resin, which requires 10 years and above. The traditional use of the leaves as tea in lowering high body temperature has been an idea for the exploration of the antipyretic properties of the leaves. The removal of moisture content by different drying techniques offers numerous advantages, which improve stability, as well as prevent microbial growth and biochemical modifications that could alter the characteristics of agricultural products. Current conventional drying methods, such as sun drying, conventional oven drying, hot air drying, and freeze-drying have disadvantages due to longer drying time, deterioration of nutrients, and physical appearance. Infrared drying is one of the latest techniques with unique characteristics, in which the heat penetrates directly into the product without losses to the surrounding. In this study, a series of experiments were conducted at various temperatures using a fabricated far-infrared (FIR) dryer and compared with a conventional oven in the drying of Aquilaria spp. leaves: Aquilaria subintegra and Aquilaria malaccensis.